Complications of nailing in closed tibial fractures. - Williams, J; Gibbons, M; Trundle, H; Murray, D; Worlock, P (1995)
Reamed intramedullary nailing was used to treat 102 closed tibial shaft fractures. Although a high rate of union was achieved (98%), we noted a higher incidence of complications than previously reported. Thirty-five (37%) patients exhibited one or more components of malunion. In 17 (18%) patients, further operative procedures were required to achieve union or to correct malalignment. New, postoperative peroneal nerve lesions were found in 19 (19%) patients, of which four (4%) failed to resolve. Acute compartment syndrome, requiring fasciotomy, developed in seven (7%) cases after surgery. Two patients developed an atrophic nonunion. In spite of these complications, the overall results were good and we continue to recommend this method of treatment for the displaced, unstable tibial shaft fracture.